2015
DOI: 10.1007/s10566-015-9342-x
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Styles in Children Living in Alternative Care: A Systematic Review of the Literature

Abstract: BackgroundA large number of children are currently living in Alternative Care. The relationship they establish with their temporary caregivers can play a significant role in their development. However, little has been published regarding attachment with temporary Caregivers.ObjectiveThe aim of this review is to analyse the existing published studies regarding attachment styles in children living in alternative care (Children’s Homes and Foster Care). The review analyses rates of attachment styles and associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 48 publications
0
25
1
2
Order By: Relevance
“…In recent years, research reviews into alternative care have reinforced these seminal findings from the works of Bowlby, Ainsworth and Rutter. For example, Garcia Quiroga and Hamilton-Giachritsis (2016) undertook a systematic review of the literature on attachment and found that attachment security for children across alternative care was negatively affected but that the impact was greater for children in institutions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research reviews into alternative care have reinforced these seminal findings from the works of Bowlby, Ainsworth and Rutter. For example, Garcia Quiroga and Hamilton-Giachritsis (2016) undertook a systematic review of the literature on attachment and found that attachment security for children across alternative care was negatively affected but that the impact was greater for children in institutions.…”
Section: Introductionmentioning
confidence: 99%
“…A partir de lo descripto, fueron seleccionados 58 artículos, de los cuales 19 corresponden a revisiones sistemáticas (Anghel, Herczog, y Dima, 2013;Bakermans-Kranenburg et al, 2011;Browne, 2017;Del Valle, Bravo y López López, 2009;Finet et al, 2016;García Quiroga y Hamilton-Giachritsis, 2016;Gómez Bengoechea y Berástegui Pedro Viejo, 2009;Gunnar y Quevedo, 2007;Heim y Nemeroff, 2001;Jaar y Córdova, 2017;Johnson y Gunnar, 2011;Kaufman et al, 2000;Martínez González, 2008;McCall, 2012;Monaghan y Haussmann, 2015;Nemeroff, 2004;Rodríguez Juárez, 2016;Van IJzen-doorn et al, 2011;World Health Organization, 2004), 4 son informes de organizaciones para la infancia (Palummo, 2013;RELAF, 2016;UNICEF, 2012;, mientras que los 35 restantes corresponden a estudios empíricos.…”
Section: Métodounclassified
“…In an attempt to ameliorate attachment insecurities between foster youth and foster parents, researchers are evaluating factors that predict secure attachment and interventions to increase secure attachment and connection (Quiroga and Hamilton-Giachritsis 2016;Wright and Edington 2016). For example, Dozier et al (2009) tested an intervention designed to teach foster parents how to provide nurturing care to young (3.6-to 39.4-month-old) foster children who did not elicit such care.…”
Section: Policy and Practice Implicationsmentioning
confidence: 99%